Monetary policy in an emerging European economic and monetary union : key issues. - Frenkel, Jacob A. (1991)
Examines the goals of monetary policy in the context of the interrelationship among price stability, current account equilibrium, and exchange rate stability. Emphasizes the importance of fiscal discipline, and evaluates alternative mechanisms for encouraging such discipline.